ESTUDIO PRELIMINAR DE COLECCIÓN DE SEMEN EN OSO DE ANTEOJOS (Tremarctos ornatus) - Enciso H., Marco (2006)
Semen was collected in a Spectacled Bear (Tremarctos ornatus) reared in captivity using the electroejaculation technique. Four series of 6 volt discharges by 15 seconds each plus manual stimulation were carried out. An effective penis erection and small volume of ejaculate was obtained in the last series of electrical stimulus. Seminal motility was 50%. Further studies are required to optimize the use of the electroejaculator in order to obtain higher volumes and better semen quality.